Identifikasi gen aroma pada progeni-progeni backcross antara varietas Ciherang dengan Pandan Wangi - Djarot Sasongko Hami Seno; Akhmad Endang Zainal Hasan; Tri Joko Santoso; Bram Kusbiantoro; Zainal Alim Mas'ud (Institut Pertanian Bogor, 2011)
Marker-assisted PCR has been considered as the most potential method for fragrant selection. RM223 is the only suitable marker to identify mutated badh2 gene of Pandan Wangi. This research applies RM223-assisted PCR in the introgression of fragrant gene (mutated badh2) of Pandan Wangi variety, to engineer non-transgenic fragrant variety with good agronomic traits as those of Ciherang. Gene introduction was carried out through site-directed crossing; Pandan Wangi was crossed and backcrossed to Ciherang until heterozygot BC5F1, followed by selfing to obtain homozygot BC5F2. RM223-assisted selection was conducted in each cross and backcross generation. RM223 was able to identify native, mutated and heterozygot badh2 of Ciherang, Pandan Wangi, and their cross/backcross progenies, respectively. Therefore, the introgression of mutated badh2 within progenies were observed, as well as the statues of badh2 gene (native/mutated) and alleles (homozygot/heterozygot). Further backcross and selfing to obtain BC5F2 is in progress.